PENYULUHAN DAN PENGOLAHAN DATA SOSIAL EKONOMI PERIKANAN - Akbar, Y Rahmat (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
Weaknesses in fisheries data and information systems are a challenge in developing a fisheries business. This data information will provide great benefits, especially in the sustainable use of fisheries resources. Optimizing the use of statistical data and analytical tools, especially quantitative, will benefit researchers in producing detailed findings and information about fisheries. This extension activity aims to increase the knowledge of lecturers, students and practitioners from related agencies in the field of fisheries in the use of data using statistical tools so that it can facilitate the processing and research, especially in the field of fisheries. The method of delivering the material is done with presentations, training and simulations, as well as questions and answers with participants who aim to find out and provide solutions to the constraints of the participants in conducting data analysis in the Social Economy of Fisheries. From the results of the counseling given, the achievement of the objectives of the service activities was seen from the participants’ understanding of the suitability of the statistical tools with the research problem, and the ability of the participants to analyze the data.